Scientific production portals - Calderón-Rehecho, Andoni (Anuario ThinkEPI, 2017)
The main aspects of how to create a CRIS (current research information system) are discussed. From several points of view, CRIS addresses the following: knowing an institution´s scientific impact; simplifying and improving institutional management; having a suitable tool for researchers to elaborate their curriculum vitae; and having a global research database, etc. To get a CRIS it is necessary for collaboration between different professional types, including librarians -who should be heavily involved-, in order to have the best and most complete information available.